REVITALIZING HYPNOTHERAPY IN FOSTERING STUDENTS’ RELIGIOUS CHARACTER THROUGH GUIDANCE AND COUNSELING IN KARAWANG - Ferianto Ferianto; Firmansyah Firmansyah; Ani Aryati; Gatot Kaca; Muhammatkasibudi Hajimasamae (Conciencia, 2025)
Instilling religious character in students constitutes an essential component of national education goals, particularly within the framework of Islamic education. Conventional approaches often fail to effectively cultivate students’ inner awareness of religious values. This study investigates the revitalization of hypnotherapy-based learning methods in fostering students’ religious character through Guidance and Counseling services in Karawang Regency. Employing a qualitative case study design, the research was conducted in three secondary schools and involved six Guidance and Counseling teachers, forty-five students, and three school principals as supporting informants. Data were collected through in-depth interviews, participatory observation, and documentation at schools that had implemented hypnotherapy-based counseling services. Thematic analysis was applied through data reduction, categorization, and source triangulation. The findings reveal that hypnotherapy holds substantial potential in facilitating the deeper internalization of religious values, as it engages the subconscious dimension of students. The revitalization of this method includes integrating spiritual values into hypnotherapy scripts, providing intensive training for Guidance and Counseling teachers, and fostering collaboration with parents and local religious leaders. These results suggest that hypnotherapy can serve not only as a psychological intervention but also as an innovative and transformative strategy for character education. The implications of this study contribute to the formulation of Islamic education policies that are more responsive to the emotional and spiritual needs of students.